A atuação dos terapeutas ocupacionais em iniciativas de geração de trabalho e renda no âmbito da saúde mental: estudo sobre a realidade do estado de São Paulo - Morato, Giovana Garcia (2014)
The work suggested in the mental health field must evidence the principles of social inclusion, which is provided by the Psychiatric Reform. Through this direction, the experiences of employment and income generation have had an important role in the psychosocial rehabilitation, once it has created the possibility to lower skilled people with different levels of autonomy to do work activities and have a monetary income from it. From the history of the occupational therapy as an occupation it is shown that the occupational therapist has a great potential to coordinate job and income creation initiatives in the mental health field developed in the actual context. The present study had as general objective the investigation of the occupational therapists who work in job and income generation initiatives in the state of São Paulo, regarding their practices. It is a descriptive transversal exploratory study, which made use of the qualitative approach. Sixteen occupational therapists distributed in ten initiatives of job and income creation in the state of São Paulo were subjects of this study. In order to collect the data, a semi-structured questionnaire and a semi-structured interview were used. The data from the questionnaire were analyzed descriptively and the interview analyzed through the Thematic Analysis technique. Out of the ten studied initiatives, five can be characterized as job and income generation services, most of them with more than five years of operation, serving only mental health users and developing production activities, and only one is not linked to the solidarity economy movement. As of the actuation of the occupational therapists, it was pointed that them develop administrative activities, related to the organization and execution of the productive process under the economic perspective, which calls these professionals to the development of a new do . In this sense, it is believed that the investment in formation of these professionals is one of the pillars to think the matter of job as an entitlement to the mental health users. It was also identified that the professionals develop their practices allied to concepts and fundamentals of the profession supported by the current public policies regarding mental health and solidarity economy, the activity being pointed in an emphatic way as a occupational therapy resource that is constantly present in the job and income generation context, in addition from taking the dimensions of the work as guidance to the developed in these contexts. It is expected that the present study contributes to the knowledge and diffusion to the practice which has been developed by occupational therapists in job and income generation, highlighting the profile currently assumed by these professionals regarding the job proposition in the mental health scope and the contributions arising from this actuation in the psychosocial rehabilitation process of people with mental disorder.